Synthetic and Natural Antioxidants Used in the Oxidative Stability of Edible Oils: An Overview - Viana da Silva, Marcondes; Santos, Mariana Romana Correia; Alves Silva, Izis Rafaela; Macedo Viana, Eduardo Bruno; Dos Anjos, Dioneire Amparo; Santos, Ingrid Alves; Barbosa de Lima, Neuma Goncalves; Wobeto, Carmen; Jorge, Neuza [UNESP]; Lannes, Suzana Caetano Da Silva (Taylor & Francis Inc, 2021)
Lipid peroxidation is a critical factor in the edible oils production chain. To minimize this process, several studies have been developed using synthetic antioxidants, which are widely used in oil processing to preserve the molecular integrity of oils. Studies indicate that antioxidants from natural sources are preferable for use in frying as well as cooking in general, as an efficient option to inhibit lipid peroxidation. In this review, we highlight the opportunities and challenges regarding the use of natural antioxidants in substitution to synthetic antioxidants in terms of the effective improvement of oxidative stability in edible vegetable oils.
Keywords: Chemical composition; lipid peroxidation; mechanism; legislation